(untitled) (Third Sector Social Economic Review, 2023)
Unlike other occupational groups, healthcare professionals also have risk faktors that vary depending on the nature of the work done. The aim of this study was to determine whether the healthcare workers’ job security views in the working environment were influenced by demographic variables. It was also conducted in order to determine whether there were differences in opinion between the health personnel working in the surgical clinic and in the dialysis unit in the hospital. The universe of the research is composed of all the health workers who are working in the Department of Surgery and Dialysis Unit in X University Hospital in Ankara. The survey sample is composed of 100 people who agreed to participate in the survey. For the data, 8 variable demographic characteristics scale and Job Safety Assessment Scale were used. All datas were evaluated by using the SPSS programme. In the evaluation, for binary variables The ’t’ test and for multiple variables the ANOVA test were used. As a result of the analysis, there is no significant difference between gender variables and job security levels. It is seen that doctors have more negative job security scores than other occupational groups. It has been found that the health professionals working in the surgical department have more negative evaluations than the dialysis department workers. Low-level experienced workers have shown more negative scores on scales of FOU (Physical Environment Compliance), KÖK(Protective Measures and Rules) and MAGD (Materials, Tools and Equipment Inspection) than others. It is observed that MAGD (Material, Tools and Equipment Inspection) scores of undergraduate graduates are more negative than those of secondary school and high school graduates.